2018
DOI: 10.1186/s12944-018-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of reduced platelet counts in patients with nonalcoholic fatty liver disease (NAFLD): a prospective cohort study

Abstract: BackgroundThe production of peripheral platelet is mainly regulated by thrombopoietin, which is a glycoprotein hormone predominantly synthesized in the liver. Previously, many studies have reported that there was an inverse correlation between the degree of chronic viral hepatitis and the peripheral platelet count. However, the effect of nonalcoholic fatty liver disease (NAFLD) on the peripheral platelet counts remains unclear.MethodsWith 1303 participants from “The prevention of MS and multi-metabolic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…Patients with NAFLD have a higher risk of having a reduced platelet count compared with people without NAFLD [ 13 ]. Recently, the effect of platelets on hepatic regeneration and suppression of fibrosis has been reported in a murine model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NAFLD have a higher risk of having a reduced platelet count compared with people without NAFLD [ 13 ]. Recently, the effect of platelets on hepatic regeneration and suppression of fibrosis has been reported in a murine model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously suggested, that different etiologies may be associated with different hepatic damage mechanisms relating to platelets which play a role in the induction of hepatic fibrosis[ 30 , 31 ]. A previous study in NAFLD, showed that PTC were decreased in cirrhotics over a 5 year follow up compared to healthy controls[ 14 ]. Additionally, a negative correlation between the PTC and the severity of liver fibrosis in NAFLD patients has been demonstrated; a linear decrease of the PTC was correlated with increasing histological fibrosis stage.…”
Section: Discussionmentioning
confidence: 99%
“…While the association between thrombocytopenia and cirrhosis is well-established, little is known about the association between subtle changes in platelet counts over time and the long-term risk of cirrhosis development. Few previous studies have shown that platelet counts may start to fall earlier in the course of NAFLD and HCV induced liver diseases[ 13 , 14 ]. Additionally, platelet counts have been incorporated into non-invasive tools for the diagnosis of liver fibrosis and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…These results are expected and simply explained by the damage of the adjacent hepatocytes resulting from tumor growth and interference with their blood supply or continues hepatocyte necrosis due to active cirrhosis or chronic active hepatitis (El-Serag and Rudolph, 2007;Okonkwo et al, 2011;Domingo et al, 2013;Baghdady et al, 2014). In addition to decreased thrombopoietin, which is a glycoprotein synthesized primarily in the liver and regulates the production of peripheral platelets (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%